Implementasi Peraturan Pemerintah Nomor 53 Tahun 2010 tentang Disiplin Pegawai Negeri Sipil - Syari, Neny Ratika; Warjio, Warjio; Kadir, Abdul (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The research objectives to be achieved are as follows: To find out how the Implementation, factors, efforts and obstacles of Government Regulation Number 53 of 2010 Concerning Discipline of Civil Servants in the Department of Youth, Sports and Tourism of Tanjungbalai City. Implementation of Government Regulation Number 53 Year 2010 Concerning Discipline of Civil Servants in the Youth, Sports and Tourism Office of Tanjungbalai City has not been carried out properly because there are still some Civil Servants who are not fully aware of even often violating existing regulations, even though, the official has held a socialization about this Government Regulation, but they also said that this Government Regulation was very helpful in improving the effective and efficient performance of civil servants in the Department of Youth, Sports and Tourism of Tanjungbalai City. The firmness of the Head of Service is not yet maximal so that there are still several employees in the Department of Youth, Sports and Tourism of the City of Tanjungbalai who are still not efficient in completing the assigned tasks and responsibilities.